أحكام الحدود وتطبيقها في شمال نيجيريا حد السرقة نموذجا - أحمد عمر أحمد
This research aims at studying the application of Islamic Punishment in northern Nigeria, because there are many problems found when applying Islamic punishment in shariah courts such as the contradiction between federal and state constitutions. Where the researcher studied the Islamic punishment in general starting with the literal and technical meaning of the Islamic word (Had) which means punishment as well as the type of Islamic punishments. He further discussed the Islamic punishments as applied by shariah courts in some northern shariah implementing states such as Zamfara, Jigawa, Kano, Kaduna, Katsina and Bauchi State. He also addressed the legal and courts system in Nigeria in general and the Islamic legal system and the shariah courts in northern Nigeria in particular. The Islamic penal codes of some of nothern states have been discussed and analyzed specifically that one of Zamfara states as it is the sample of which has been adopted by other shariah implementing states with highlighting differences if any. Two methodologies have been used in this research, including: The inductive theoretical method; where the researcher studied the issue of Islamic punishment in general and the punishment of theft in particular by looking in to the relevant Fiqh books, thesis, articles, legal documents and reports which are stored in libraries and websites. The researcher also used applied analytical method; where He studied the Islamic punishment cases that were applied in the Shariah courts in northern Nigeria, especially with regard to the theft, and studied the obstacles in applying these punishments in order to find appropriate solutions. The researcher has reached a number of outcomes, among of which Islamic law is the best system to be applied to achieve permanent happiness here and the Hereafter; that the application of Islamic punishments also contributes effectively to the elimination of crimes that are many in Nigerian society, especially in the northern states. Among the outcome is the comptability between Islamic penal code enacted by the nothern states goverenment with the shariah in many sections, and many of the court rulings are shariah compliant. The researcher recommends that all the solutions mentioned in the study be carried out by leaders for the better implementation of Islamic punishments; they should also develop the Islamic Penal code in order to be shariah compliant in all sections; it is necessary for the courts to follow all the guidelines put in place by the shariah while ruling; the enforcment of all rulings issued by shariah courts is also recommended by the researhcer. Furthermore, he recommends that more attention should be given by other researchers to the study the matter of Shari'ah law and address obstacles that might prevent its proper application.